Presumptions for the Integration of Green Hydrogen and Biomethane Production in Wastewater Treatment Plants - Ralfas Lukoševičius; Sigitas Rimkevičius; Raimondas Pabarčius (Applied Sciences)
Achieving climate neutrality goals is inseparable from the sustainable development of modern cities. Municipal wastewater treatment plants (WWTP) are among the starting points when moving cities to Net-zero Greenhouse Gas (GHG) emissions and climate neutrality. This study focuses on the analysis of the integration of green hydrogen (H2) and biomethane technologies in WWTPs, and on the impact of this integration on WWTPs’ energy neutrality. This study treats WWTP as an integrated energy system with certain inputs and outputs. Currently, such systems in most cases have a significantly negative energy balance, and, in addition, fossil fuel energy sources are used. Key findings highlight that the integration of green hydrogen production in WWTPs and the efficient utilization of electrolysis by-products can make such energy systems neutral or even positive. This study provides an analysis of the main technical presumptions for the successful integration of green hydrogen and biomethane production processes in WWTP. Furthermore, a case study of a real wastewater treatment plant is presented.